Nail abnormalities in patients with vitiligo - Ilteris Oguz Topal; Sule Gungor; Ozgur Emek Kocaturk; Hatice Duman; Mustafa Durmuscan (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: Vitiligo is an acquired pigmentary skin disorder affecting 0.1-4% of the general population. The nails may be affected in patients with an autoimmune disease such as psoriasis, and in those with alopecia areata. It has been suggested that nail abnormalities should be apparent in vitiligo patients. Objective: We sought to document the frequency and clinical presentation of nail abnormalities in vitiligo patients compared to healthy volunteers. We also examined the correlations between nail abnormalities and various clinical parameters. Methods: This study included 100 vitiligo patients and 100 healthy subjects. Full medical histories were collected from the subjects, who underwent thorough general and nail examinations. All nail changes were noted. In the event of clinical suspicion of a fungal infection, additional mycological investigations were performed. Results: Nail abnormalities were more prevalent in the patients (78%) than in the controls (55%) (p=0.001). Longitudinal ridging was the most common finding (42%), followed by (in descending order): leukonychia, an absent lunula, onycholysis, nail bed pallor, onychomycosis, splinter hemorrhage and nail plate thinning. The frequency of longitudinal ridging was significantly higher in patients than in controls (p<0.001). Conclusions: Nail abnormalities were more prevalent in vitiligo patients than in controls. Systematic examination of the nails in such patients is useful because nail abnormalities are frequent. However, the causes of such abnormalities require further study. Longitudinal ridging and leukonychia were the most common abnormalities observed in this study.